Magnetic EDTA Functionalized Preyssler Cross Linked Chitosan Nanocomposite for Adsorptive Removal of Pb(II) Ions. Issue 10 (4th September 2017) - Tanhaei, Bahareh; Ayati, Ali; Bamoharram, Fatemeh F.; Sillanpää, Mika
Abstract : In this study, the magnetic ethylenediaminetetraacetic acid (EDTA) modified Preyssler/chitosan/Fe3 O4 nanoparticles composite (EDTA‐PCF) was introduced as a novel adsorbent for Pb(II) ions removal from aqueous solutions. The characterization study of the prepared EDTA‐PCF was carried out by Fourier transform infrared spectrometer (FTIR), scanning electron microscopy (SEM) and N2 adsorption‐desorption isotherms. The adsorption activity of EDTA‐PCF was evaluated by the effect of adsorbent dosage, pH and contact time on the Pb(II) ions removal. The optimum values for adsorbent dosage and pH were 1.2 g/L and 5.3, respectively (>99% removal efficiency for [Pb 2+ ] = 10 mg/L). In addition, the kinetic study was carried out using pseudo‐first order, pseudo‐second order, Bangham, Elovich, and Weber and Morris models and also the Langmuir, Freundlich, and Temkin isotherm models were applied for isothermal study. The results revealed that the pseudo‐second‐order rate model and Langmuir adsorption model can well describe the adsorption process of Pb(II) ions onto EDTA‐PCF. The Weber and Morris model proposed that film and intra‐particle diffusion were involved in this adsorption process. The maximum adsorption capacity of Pb(II) onto EDTA‐PCF was estimated to be 25.9 mg/g at 25°C. Abstract : In this study, the Preyssler acid, as a unique green solid acid compound, was grafted on magnetic chitosan and modified with the EDTA to design a novel adsorbent with excellent and fast Pb‐binding ability. It was used for the adsorption of lead ions from aqueous solutions, which are potentially toxic to human.